EFEKTIVITAS PENGGUNAAN MODUL LARUTAN PENYANGGA BERBASIS PENDEKATAN SAINTIFIC DENGAN MENERAPKAN TEKNIK PROBING DAN PROMTING TERHADAP HASIL BELAJAR SISWA KELAS XI MIA SMA PADANG - Putri, W (rc-institut, 2019)
Buffer solution is one of the subjects in chemistry that studies concepts and calculations. Therefore, teaching materials are needed in the form of learning modules to guide students in finding concepts, where in the learning module there are probing and promting techniques. This study aims to reveal the effectiveness level of the scientific approach based learning module by applying probing and promting techniques to learning outcomes XI MIA SMA students. This research was conducted in two schools, namely the SMA Development Laboratory of UNP and SMAN 5 Padang. This type of research is quasi-experimental research with the design of the Randomized Control Group Posttest Only Design through a purposive sampling technique. The object of research is student learning outcomes. The research instrument used was a test of student learning outcomes in the form of 25 objective questions according to the learning objectives. Based on data analysis shows that the subject is normally distributed and homogeneous so that it can be carried out t-test for SMA UNP Laboratory Development, the value of t ? t1-? is 5.476> 1.684 then Ho is rejected and  SMAN 5 Padang is obtained value t ? t1-? is 3596> 1,126 then rejected by Ho. This means that the experimental class learning outcomes are higher than the control class significantly. Based on data analysis shows the use of buffer solution learning modules based on scientific approach with probing and promting techniques proven effective against learning outcomes with a high category.